Variability of Ratings in the Otolaryngology Standardized Letter of Recommendation. (February 2016) - Kominsky, Alan H.; Bryson, Paul C.; Benninger, Michael S.; Tierney, William S.
Objective: To determine the variability of ratings given to students on the otolaryngology standardized letter of recommendation (SLOR). Study Design: Retrospective review. Setting: Academic otolaryngology training program. Subjects and Methods: 496 SLORs to the Cleveland Clinic Otolaryngology Training Program were reviewed. The SLORs were extracted from the applications and analyzed. The distributions of ratings across the 10 categories were statistically analyzed including distribution and standard deviation. Rankings were grouped into deciles for this analysis. Results: Ratings across the 10 domains revealed clustering of results across the top 2 deciles. The distribution of the bell-shaped curve was shifted significantly to the left, representing the upper deciles. No evidence of gender or geographic bias was found. Longer length of time of association between the applicant and the letter writer correlated to a higher ranking. Conclusion: The explosion of applications being sent out by candidates for otolaryngology residency programs has prompted the implementation of the SLOR. The lack of variation in the ratings across the 10 domains does not allow for differentiation among student applicants. Reliance on the narrative letter of recommendation attached to the SLOR still remains the most significant way to differentiate among applicants. Refinements will need to be made in either the structure or use of the SLOR for it to be a more useful tool.